Susac syndrome and pregnancy: a review of published cases and considerations for patient management - Willekens, Barbara (Ther Adv Neurol Disord, 2021)
Susac syndrome (SuS) is a rare autoimmune endotheliopathy leading to hearing loss, branch retinal artery occlusions and encephalopathy. Young females are more frequently affected than males, making counselling for family planning an important issue. We reviewed published cases on SuS during pregnancy or in the postpartum period, and selected 27 reports describing the details of 33 patients with SuS. Treatment options and implications for pregnancy and breastfeeding are discussed. We propose new areas for research and suggest a management strategy.